A test of manganese effects on decomposition in forest and cropland sites. (February 2019) - Sun, Tao; Cui, Yalan; Berg, Björn; Zhang, Quanquan; Dong, Lili; Wu, Zhijie; Zhang, Lili
Abstract: Litter of plant origin is the main source of soil organic matter, and its physical and chemical quality and decomposition rates are key variables in the prediction and modelling of how litter-derived carbon (C) is cycling through the ecosystem. However, the biological control factors for decomposition are not well understood and often poorly represented in global C models. These are typically run using simple parameters, such as nitrogen (N) and lignin concentrations, characterizing the quality of the organic matter input to soils and its accessibility to decomposer organisms. Manganese (Mn) is a key component for the formation of manganese peroxidase (MnP), an important enzyme for lignin degradation. However, the functional role of Mn on plant litter decomposition has been rarely experimentally examined. Here, using a forest and a cropland site we studied, over 41 months, the effects of Mn fertilization on MnP activity and decomposition of eight substrates ranging in initial lignin concentrations from 9.8 to 44.6%. Asymptotic decomposition models fitted the mass loss data best and allowed us to separately compare the influence of Mn fertilization on different litter stages and pools. Across substrates, Mn fertilization stimulated decomposition rates of the late stage where lignin dominates decomposition, resulting in smaller fraction of slowly decomposing litter. The increased MnP activity caused by Mn fertilization provided the mechanism explaining the stimulated decomposition in the Mn-addition treatments. Highlights: Asymptotic decomposition models best fit data for remaining mass. Mn fertilization stimulated decomposition rates in late stages of decomposition. Increased decomposition rates in late stage of decomposition were clearly linked to the activity of manganese peroxidase. Mn cycle in ecosystems has important implications for predicting C residence time in soil.